Использование квантовых точек InSb в термофотовольтаических преобразователях на основе GaSb - Andronova, E. V.; Baganov, E. A.; Dalechin, A. Yu.; Karmanny, A. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The influence of radiation absorption in InSb quantum dots (QDs) on the efficiency of GaSb‑based thermophotovoltaic (TPV) elements has been investigated. It is shown that the introduction of QDs significantly expands the spectral range of photosensitivity and increases the efficiency of TPV elements. Analysis of optical transitions in InSb QDs, as well as the dependence of the thermodynamic efficiency of the TPV element on QD size, made it possible to determine the optimal conductivity type, doping level of the matrix material, and select the optimal QD diameter.